Requirement of Trichome Formation for the Growth-promoting Effects of Olivine for Enhanced Weathering in Arabidopsis thaliana - Minoru Ueda; Daisuke Todaka; Satoshi Takahashi; Junko Ishida; Maho Tanaka; Tokihiro Ikeda; Keiko Suzuki; Misako Miwa; Takeshi Uchiyama; Yasuhiro Ishimaru; Kazuhiro Sayama; Nobuyuki Uozumi; et al. (Journal of Plant Growth Regulation, 2026)
Enhanced rock weathering helps remove CO 2 from air and cools the Earth over geological time periods, while also promoting plant growth, but the molecular mechanism underlying enhanced plant growth is unclear. In this study, ionome and transcriptome analyses revealed the importance of trichome formation for the growth-promoting effects of olivine ground to enhance weathering. In Arabidopsis, the application of 10% (w/w) olivine improved plant growth (a 64.2% increase in leaf area) and caused a 24.7% increase in Mg accumulation determined by ICP-AES at 23 days after germination (DAG) under long-day (16 h light/8 h dark cycle) conditions. Elemental maps of olivine-treated plants at 10 DAG produced by micro-particle-induced x-ray emission showed that olivine significantly altered Mg, K, and S accumulation in trichomes on true leaves, suggesting that trichomes may be critical for olivine-induced growth. The growth of glabrous1 ( gl1-1 and gl1-4 ) mutants defective in trichome initiation was not promoted by olivine. A transcriptome analysis of shoots by RNA-seq from wild-type plants at 16 DAG indicated olivine suppressed biotic stress-responsive gene expression. Additionally, Zn homeostasis was disrupted by olivine in gl1 mutants, implying that decreased Zn availability may inhibit the positive effect of olivine on growth. Collectively, our data uncovered the importance of trichomes to the adaptation of plants to soils containing rock-powders for crop improvement and agricultural sustainability and suggest the possibility that applying olivine might modulate the growth–defense trade-off governed by ion homeostasis mediated through trichome development, leading to improved plant growth.

Tree retention for conserving saproxylic beetles in harvested conifer plantations - Satoshi Yamanaka; Akira Ueda; Naoyuki Furuya; Takuya Kobayashi; Hideaki Goto; Kenichi Ozaki (Forest Ecology and Management, 2025)

A Pyrazole Partially Induces Brassinosteroid-Related Gene Expression, Leading to Salt Stress Sensitivity - Minoru Ueda; Satoshi Takahashi; Junko Ishida; Ayumi Yamagami; Takeshi Nakano; Florian Pünner; Mai Akakabe; Yoshihiro Sohtome; Atsushi J. Nagano; Mikiko Sodeoka; Motoaki Seki (Journal of Plant Growth Regulation, 2025)

Y-Ho fractionation during basalt alteration in hydrothermal system: An implication for superchondritic Y/Ho signature recorded in Precambrian banded iron formations - Satoshi Yoshida; Hisahiro Ueda; Hisashi Asanuma; Yusuke Sawaki (Chemical Geology, 2024)

Retention forestry in plantations: Synthesizing key findings of early studies from a long-term experiment in northern Japan - Kenichi Ozaki; Nobuhiro Akashi; Kazuhiro Kawamura; Keisuke Obase; Akira Ueda; Akira Unno; Satoshi Yamanaka; Yuichi Yamaura (Forest Ecology and Management, 2024)

Rendezvous trajectory design of logistics resupply missions to the lunar gateway in near-rectilinear halo orbit - Ryo Nakamura; Junji Kikuchi; Takahiro Sasaki; Yuki Matsumoto; Moeko Hidaka; Naomi Murakami; Satoshi Ueda; Naoki Satoh (Journal of Space Safety Engineering, 2023)

Dietary nitrate does not acutely enhance skeletal muscle blood flow and vasodilation in the lower limbs of older adults during single-limb exercise - William E. Hughes; Nicholas T. Kruse; Kenichi Ueda; Andrew J. Feider; Satoshi Hanada; Joshua M. Bock; Darren P. Casey (European Journal of Applied Physiology, 2020)

A Strategy for Co-former Selection to Design Stable Co-amorphous Formations Based on Physicochemical Properties of Non-steroidal Inflammatory Drugs - Hiroshi Ueda; Noriyuki Muranushi; Satoshi Sakuma; Yasuo Ida; Takeshi Endoh; Kazunori Kadota; Yuichi Tozuka (Pharmaceutical Research, 2016)

Isolation of side population cells from endometrial cancer cells using a violet laser diode - Satoshi Tomiyasu; Tomoyuki Miyamoto; Michihiro Mori; Takahiro Yaguchi; Hiromasa Yakushiji; Setsuyo Ohno; Yasuyuki Miyake; Takuya Sakaguchi; Masatsugu Ueda; Eiji Ohno (Human Cell, 2014)

Effects of anesthesia and surgery on U crit performance and MO2 in chum salmon, Oncorhynchus keta - Kazufumi Hayashida; Hisaya Nii; Takatoshi Tsuji; Koji Miyoshi; Satoshi Hamamoto; Hiroshi Ueda (Fish Physiology and Biochemistry, 2013)

Genomic and serological detection of bat coronavirus from bats in the Philippines - Shumpei Tsuda; Shumpei Watanabe; Joseph S. Masangkay; Tetsuya Mizutani; Phillip Alviola; Naoya Ueda; Koichiro Iha; Satoshi Taniguchi; Hikaru Fujii; Kentaro Kato; Taisuke Horimoto; Shigeru Kyuwa; et al. (Archives of Virology, 2012)

Detection of bat coronaviruses from Miniopterus fuliginosus in Japan - Kazuya Shirato; Ken Maeda; Shumpei Tsuda; Kazuo Suzuki; Shumpei Watanabe; Hiroshi Shimoda; Naoya Ueda; Koichiro Iha; Satoshi Taniguchi; Shigeru Kyuwa; Daiji Endoh; Shutoku Matsuyama; et al. (Virus Genes, 2012)

Sighting survey of cetaceans in the Tsugaru Strait, Japan - Ryusuke SUDO; Maya URANISHI; Takuma KAWAMINAMI; Mika IHARA; Satoshi IIZUKA; Mari UEDA; Md Monir HOSSAIN; Takashi MATSUISHI (Fisheries Science, 2008)

Inverse relationship between serum erythropoietin and blood lead concentrations in Kathmandu tricycle taxi drivers - Susumu Sakata; Satoshi Shimizu; Kumiko Ogoshi; Kazuko Hirai; Yoshimi Ohno; Takashi Kishi; Jeevan B. Sherchand; Masako Utsumi; Munetaka Shibata; Miyako Takaki; Masatsugu Ueda; Ippei Mori (International Archives of Occupational and Environmental Health, 2007)

Heterologous expression of a mammalian ABC transporter in plant and its application to phytoremediation - Kazufumi Yazaki; Nao Yamanaka; Tsugumi Masuno; Satoshi Konagai; Nobukazu Shitan; Shuji Kaneko; Kazumitsu Ueda; Fumihiko Sato (Plant Molecular Biology, 2006)

Heterologous Expression of a Mammalian ABC Transporter in Plant and its Application to Phytoremediation - Kazufumi Yazaki; Nao Yamanaka; Tsugumi Masuno; Satoshi Konagai; Shuji Kaneko; Kazumitsu Ueda; Fumihiko Sato (Plant Molecular Biology, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Approach for functional analysis of glycan using RNA interference - Shoko Nishihara; Ryu Ueda; Satoshi Goto; Hidenao Toyoda; Hideki Ishida; Mitsuru Nakamura (Glycoconjugate Journal, 2004)